SMART SAFETY SHOES: INTERNET OF THINGS BASED ANTI FATIGUE SENSORS TO PREVENT MUSCULOSKELETAL DISORDERS - Hafidhuddin, Rohmat Fais Sahhal; Rahmawati, Novia Hayu; Jamaludin, Mukhammad; Disrinama, Am Maisarah (Journal of Vocational Health Studies, 2021)
Background: Occupational injuries in Indonesia increase every year where one of the causes is fatigue. Musculoskeletal disorders (MSDs) is the most common occupational injuries that happen. This problem can be caused by ergonomic factors such as standing position for long periods of time. Purpose: Safety shoes can be personal protective equipment to prevent MSDs complaints on the feet. Method: Additional designs and features are needed to increase the effectiveness of safety shoes. Smart Safety Shoes are shoes equipped with anti-fatigue sensors where there is a pulse detector and a heating sensor and apply Internet of Things technology by focusing attention to ergonomic concepts. The sensor system in the shoes is connected to the android application via wifi network. The application displays pulse rate, temperature, oxygen saturation, warning and recommendation information, as well as heating sensor control. Result: From the results of trials using a random sample, the levels of comfort and safety of these shoes are 83,3% and 83,3%, so they are quite effective to use. Conclusion: Foot fatigue can be relieved by turning on the heating sensor for about 5-10 minutes for maximum comfort so that MSDs can be prevented as early as possible.